2018
DOI: 10.1016/s0140-6736(18)30482-3
|View full text |Cite|
|
Sign up to set email alerts
|

Tackling socioeconomic inequalities and non-communicable diseases in low-income and middle-income countries under the Sustainable Development agenda

Abstract: Five Sustainable Development Goals (SDGs) set targets that relate to the reduction of health inequalities nationally and worldwide. These targets are poverty reduction, health and wellbeing for all, equitable education, gender equality, and reduction of inequalities within and between countries. The interaction between inequalities and health is complex: better economic and educational outcomes for households enhance health, low socioeconomic status leads to chronic ill health, and non-communicable diseases (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
222
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(241 citation statements)
references
References 78 publications
11
222
0
8
Order By: Relevance
“…36 Low education corresponds to ISCED 0-1, Intermediate education to ISCED 2-4 and High education to ISCED 5-6. 1 Adjusted for age, sex, alcohol drinking, tobacco smoking, race/ethnicity, fruit and vegetable consumption and study center (for multicenter studies).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Low education corresponds to ISCED 0-1, Intermediate education to ISCED 2-4 and High education to ISCED 5-6. 1 Adjusted for age, sex, alcohol drinking, tobacco smoking, race/ethnicity, fruit and vegetable consumption and study center (for multicenter studies).…”
Section: Discussionmentioning
confidence: 99%
“…National and international agencies are implementing strategies to guarantee health and wellbeing for all people by targeting sustainable development goals like education, gender equality and poverty reduction. 1 Worldwide, there is increasing awareness and evidence that low socioeconomic position (SEP) is a strong determinant of morbidity and premature mortality from selected noncommunicable diseases, including several cancers. 2,3 SEP reflects the availability of cultural, material and social resources that translate into advantages in terms of decision making, social network, lifestyle habits and also access to health services.…”
Section: Introductionmentioning
confidence: 99%
“…Once viewed as chronic diseases of aging populations, obesity and its comorbidities are increasingly affecting younger populations who are politically active, engaged in the workforce, and have dependants. As with HIV, there are complex linkages between low socio‐economic status and NCDs and their risk factors, including obesity, in some countries . In both cases, effective public policy responses risk becoming derailed by an excessive focus on individual behaviour and personal responsibility, rather than health systems that exclude large numbers of people, and health‐harming and exploitative environments.…”
Section: Commonalities Between the Global Pandemics Of Obesity And Humentioning
confidence: 99%
“…As with HIV, there are complex linkages between low socio-economic status and NCDs and their risk factors, including obesity, in some countries. 34,35 In both cases, effective public policy responses risk becoming derailed by an excessive focus on individual behaviour and personal responsibility, rather than health systems that exclude large numbers of people, and health-harming and exploitative environments. There is no magic bullet in sight-an HIV vaccine and a cure for AIDS remain elusive, while treatments for diabetes mellitus, cardiovascular disease, cancer, osteoarthritis, hypertension, and stroke are often expensive and offer no promise of a lifetime cure.…”
Section: Commonalities Between the Global Pandemics Of Obesity And mentioning
confidence: 99%
“…The review,1 published by the Lancet ’s taskforce on non-communicable diseases and economics, showed that the burden of preventable non-communicable diseases associated with tobacco, alcohol, and obesity is itself regressive.…”
mentioning
confidence: 99%